Peningkatan Pengetahuan Dan Deteksi Dini Hipertensi Pada Lansia - Santi Herlina; Wiwin Winarti; Diah Tika Anggraeni; Nadia Shahidda; Nirmala; Aulia Marshanda Apsarie; Sila Aimanatul Afifah; Putri Rahayu (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Hypertension is a silent killer disease that is often not felt so when someone comes to a health facility with a complicated condition. Hypertension in Indonesia has increased from the previous 25.8% in 2013 to 34.11% in 2018. Age is one of the risk factors for this disease. The incidence rate at the age of 75 years and over is 69.53%. The purpose of this activity is to determine the level of knowledge about hypertension, conduct early detection targeting the elderly with implementation methods in the form of education and health checks (measurement of blood pressure, current blood sugar and nutritional status). The results showed that the average age of the elderly was 59 years with the lowest age being 52 years and the highest being 77 years, all genders were female, the knowledge of the elderly was 100% good after being educated, 36.8% of the elderly had a history of hypertension, 26.3% who had been drinking regularly. medication, 52.6% who received family support in the management of hypertension. The average blood pressure of the elderly is 131/86mmHg. The average value of blood sugar while (GDS) is 165 g/dl. Nutritional status in the elderly seen from the average BMI is 25.9. Management of hypertension needs to involve all elements, both from patient compliance and from the surrounding environment, especially families, therefore providing information through education can improve understanding of the elderly and early detection as part of prevention to prevent further complications. Community-based preventive programs need to be improved along with the increasing incidence of hypertension.